2021
DOI: 10.1093/cercor/bhab067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes in the 16p11.2 Locus during Development of the Human Fetal Cerebral Cortex

Abstract: The 593 kbp 16p11.2 copy number variation (CNV) affects the gene dosage of 29 protein coding genes, with heterozygous 16p11.2 microduplication or microdeletion implicated in about 1% of autism spectrum disorder (ASD) cases. The 16p11.2 CNV is frequently associated with macrocephaly or microcephaly indicating early defects of neurogenesis may contribute to subsequent ASD symptoms, but it is unknown which 16p11.2 transcripts are expressed in progenitors and whose levels are likely, therefore, to influence neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Loss of PA1 in embryos leads to severe developmental defects that occur in E8.0 and no homozygous mutant has survived to E10.5, most likely due to decreased expression of BMP2 [ 21 ]. Recently, PA1 was found to be expressed in the human fetal cerebral cortex, and a homozygous missense mutation (c.274A > G; p.Ser92Gly, NM_024516.4) was found to be associated with severe neurodevelopmental disorders [ 22 , 23 ]. In addition, PA1 has been found to cooperate with phosphorylated CREB (pCREB) and glucocorticoid receptor (GR) to regulate the expression of key adipose differentiation transcription factors C/EBPβ and C/EBPδ, and the deletion of Pa1 in white and brown preadipocytes has been shown to severely disrupt adipogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of PA1 in embryos leads to severe developmental defects that occur in E8.0 and no homozygous mutant has survived to E10.5, most likely due to decreased expression of BMP2 [ 21 ]. Recently, PA1 was found to be expressed in the human fetal cerebral cortex, and a homozygous missense mutation (c.274A > G; p.Ser92Gly, NM_024516.4) was found to be associated with severe neurodevelopmental disorders [ 22 , 23 ]. In addition, PA1 has been found to cooperate with phosphorylated CREB (pCREB) and glucocorticoid receptor (GR) to regulate the expression of key adipose differentiation transcription factors C/EBPβ and C/EBPδ, and the deletion of Pa1 in white and brown preadipocytes has been shown to severely disrupt adipogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analysis of human fetal gene expression data found that KIF22 and ALDOA are significantly enriched in progenitors compared to post-mitotic cells making them candidates for having specific roles in neurogenesis in the developing human fetal cerebral cortex. It has been suggested that neurogenesis is disrupted in 16p11.2 CNVs ( Morson et al, 2021 ). The participants in our study with rare variants in ALDOA, KIF22, TAOK2 and SEZ6L2 did not present with ASD or neurodevelopmental disorders ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated ventral telencephalic differentiation might also occur in humans with 16p11.2 deletion, as we observed in ventral organoids. Indeed, many 16p11.2 genes, such as KIF22, ALDOA, HIRIP3, PAGR1, and MAZ were found to be expressed in progenitors and could, therefore, influence neurogenesis (Roth et al, 2020, Morson et al, 2021). To date, only one study utilised organoids to examine the effect of 16p11.2 deletion on cortical NPC proliferation at one month, revealing a decreased proliferation rate and higher NEUN+ cells (Urresti et al, 2021), which is in line with our findings in ventral organoids.…”
Section: Discussionmentioning
confidence: 99%